Hybrid PWM noise cancellation technique to reduce switching losses for two‐segment three‐phase motor. Issue 8 (25th June 2019) - Huang, Yingliang; Xu, Yongxiang; Zhang, Wentao; Zou, Jibin
Abstract : This study proposed a novel method to eliminate the pulse width modulation (PWM) harmonics at a quite low switching frequency for the two‐segment three‐phase motor. Due to the PWM technique and considerations of switching losses, acoustic noise <20 kHz in the motor drive system is common. By using modified space vector PWM (MSVPWM) technique and interleaved topology with magnetically coupled inductors (MCIs), the proposed novel method is able to remove the first, second, and third order carrier frequency noises from the motor. The MSVPWM is used to eliminate the first and third order carrier frequency harmonics and second order harmonics are reduced by interleaved topology. With this method, the unpleasant acoustic noise <20 kHz could be removed when the switching frequency is selected near 6.7 kHz. The size of MCIs mainly depends on the PWM current harmonics and it is very small compared with inductor‐capacitor/inductor‐capacitor‐inductor filter. Moreover, this method remains to be the control dynamics of the motor without additional inductance for fundamental frequency currents. Finally, the effectiveness of the proposed method is verified by detailed simulation and experimental results.